Expression of Functional Anti-p24 scFv 183-H12-5C in HEK293T and Jurkat T Cells - Che Omar, Mohammad Tasyriq (Tabriz University of Medical Sciences, 2017)
Purpose: More than half of the diagnostic and therapeutic recombinant protein production depends on mammalian-based expression system. However, the generation of recombinant antibodies remains a challenge in mammalian cells due to the disulfide bond formation and reducing cytoplasm. Therefore, the production of functional recombinant antibodies in target cell line is necessary to be evaluated before used in therapeutic application such intrabodies against HIV-1. Methods: The work was to test expression of a single-chain variable fragment (scFv) antibody against HIV-1 Capsid p24 protein in a human mammalian-based expression system using HEK293T and Jurkat T cells as a model. Three expression plasmid vectors expressing scFv 183-H12-5C were generated and introduced into HEK293T. Expression of the scFv was analyzed, while ELISA and immunoblotting analysis verified its binding. The evaluation of the recombinant antibody was confirmed by HIV-1 replication and MAGI infectivity assay in Jurkat T cells. Results: Three plasmid vectors expressing scFv 183-H12-5C was successfully engineered in this study. Recombinant antibodies scFv (~29 kDa) and scFv-Fc (~52 kDa) in the cytoplasm of HEK293T were effectively obtained by transfected the cells with engineered pCDNA3.3-mu-IgGk-scFv 183-H12-5C and pCMX2.5-scFv 183-H12-5C-hIgG1-Fc plasmid vectors respectively. scFv and scFv-Fc are specifically bound recombinant p24, and HIV-1 derived p24 (gag) evaluated by ELISA and Western blot. Jurkat T cells transfected by pCDNA3.3-scFv 183-H12-5C inhibit the replication-competent NL4-3 viral infectivity up to 60%. Conclusion: Anti-p24 scFv 183-H12-5C antibody generated is suitable to be acted as intrabodies and may serve as a valuable tool for the development of antibody-based biotherapeutics against HIV-1.